Treaty of Friendship, Commerce, and Navigation between the Hanseatic Republics and the Kingdom of Siam, Signed at Bangkok, October 5, 1858 - His Majesty s Command (The Royal Printing Press, 1864)
11, 11, 7, 9, 7, 8, 7, 14-22 p